2002
DOI: 10.1007/s00436-002-0665-9
|View full text |Cite
|
Sign up to set email alerts
|

Serological detection of exposure to Cryptosporidium parvum in cattle by ELISA and its evaluation in relation to coprological tests

Abstract: We evaluated serum examination as an alternative to fecal analysis for the diagnosis of exposure to Cryptosporidium parvum in cattle. The accuracy of the serum ELISA was compared to the combined results of concentration flotation microscopy and fecal enzyme immunoassay. The expected performance of the serum ELISA at different levels of infection with C. parvum was evaluated using the predicative values positive and negative. Optimal conditions for the serum ELISA can be achieved by diluting the serum samples 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Previously, when serological techniques were used to detect Cryptosporidium infection rates of 30.4% (61/201) in Gonghe and 36.8% (82/223) in Qilian were found. We detected a lower prevalence with microscopic diagnosis (20.2% in Gonghe) or PCR (28.2% in Qilian) [20], in agreement with a previous report that serological tests have a higher prevalence rate than microscopic or PCR-based diagnosis [29]. The infection rates of 36.2% (85/235) found in Huangyuan was higher than that found in a previous study which utilized microscopic diagnoses and found an infection rate of 30.6% (26/85) [30].…”
Section: Discussionsupporting
confidence: 92%
“…Previously, when serological techniques were used to detect Cryptosporidium infection rates of 30.4% (61/201) in Gonghe and 36.8% (82/223) in Qilian were found. We detected a lower prevalence with microscopic diagnosis (20.2% in Gonghe) or PCR (28.2% in Qilian) [20], in agreement with a previous report that serological tests have a higher prevalence rate than microscopic or PCR-based diagnosis [29]. The infection rates of 36.2% (85/235) found in Huangyuan was higher than that found in a previous study which utilized microscopic diagnoses and found an infection rate of 30.6% (26/85) [30].…”
Section: Discussionsupporting
confidence: 92%
“…Given there was little agreement between serum ELISA and fecal tests on samples collected from adult cows [17], serological assays should be used to support fecal examinations. The reported infection rate of randomly selected inhabitants in Seoul was only 0.5% [18], whereas another report identified that the majority (94.6%) of oocyst-positive cases were people over 50 yr of age [19].…”
Section: Discussionmentioning
confidence: 99%
“…The serological study by ELISA had a high sensitivity and low specificity [13]. In the present study, the infection of C. parvum was investigated by using an ELISA technique.…”
Section: Discussionmentioning
confidence: 99%